Assessing Technology Acceptance for SIAKAD Usage among Scholarly Community - Meinarini Catur Utami; Yuni Sugiarti; Muhammad Sanul Akbar; Muhammad Qomarul Huda; Qurrotul Aini (LPPM Universitas Bhinneka Nusantara, 2026)
The deployment of academic information systems in higher education institutions necessitates both technological preparedness and user acceptance to guarantee sustained utilization. In practice, users frequently encounter challenges, including confusion when retrieving academic material, doubts regarding the accuracy of presented data, and dependence on manual verification despite the system's availability. Such circumstances diminish trust and render the system seen as a mere formal obligation rather than a beneficial academic resource. Differences in user perceptions of system quality, information quality, and behavioral aspects consequently affect the efficacy of system adoption. By integrating UTAUT 2 with the Delone & Mclean Model, this research aims to analyse the variables that influence user acceptance and the usage behaviour of the current academic information system. A quantitative explanatory approach was employed, utilizing survey data collected from 450 active users. PLS-SEM was employed to examine the data for the assessment of both measurement and structural models. The findings demonstrate that performance expectancy, effort, facilitating conditions, habit, system quality, and knowledge all have a substantial impact on behavioral intention and usage behavior. Conversely, social influence does not substantially impact behavioral intention, indicating that system utilization is primarily motivated by functional requirements rather than normative pressure. Practically, the results suggest that universities should prioritize system reliability, accurate and timely academic information, responsive user support, and routine integration of SIAKAD into core academic workflows to strengthen continued usage.